2012
DOI: 10.1242/jeb.072223
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Na+, K+ and Cl− activities in Acheta domesticus Malpighian tubules and the response to a diuretic kinin neuropeptide

Abstract: SUMMARY The mechanism of primary urine production and the activity of a diuretic kinin, Achdo-KII, were investigated in Malpighian tubules of Acheta domesticus by measuring intracellular Na+, K+ and Cl− activities, basolateral membrane voltage (Vb), fluid secretion and transepithelial ion transport. Calculated electrochemical gradients for K+ and Cl− across the basolateral membrane show they are actively transported into principal cells, and basolateral Ba2+-sensitive K+ channels do not contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Ca 2+ is moved from cell-to-lumen thermodynamically uphill by active Ca 2+ exporting pumps since both chemical (∼1000-fold) and electrical (V apical = +71 mV lumen-positive) gradients across apical membranes of A. domesticus tubules oppose Ca 2+ entry into the lumen (Coast, 2012). Plasma membrane Ca 2+ -ATPase (PMCA) pumps have been localized to the apical membranes in tubules of the gypsy moth, Lymantria dispar (Pannabecker, Smith, Beyenbach, & Wasserman, 1995).…”
Section: It Is Well Established That Malpighian Tubules Of Insects (Amentioning
confidence: 99%
See 1 more Smart Citation
“…Ca 2+ is moved from cell-to-lumen thermodynamically uphill by active Ca 2+ exporting pumps since both chemical (∼1000-fold) and electrical (V apical = +71 mV lumen-positive) gradients across apical membranes of A. domesticus tubules oppose Ca 2+ entry into the lumen (Coast, 2012). Plasma membrane Ca 2+ -ATPase (PMCA) pumps have been localized to the apical membranes in tubules of the gypsy moth, Lymantria dispar (Pannabecker, Smith, Beyenbach, & Wasserman, 1995).…”
Section: It Is Well Established That Malpighian Tubules Of Insects (Amentioning
confidence: 99%
“…It is well established that Malpighian tubules of insects (A. domesticus, Teleogryllus oceanicus, D. melanogaster, Rhodnius prolixus) secrete calcium into the primary urine, contributing to the elimination of excess dietary calcium (Maddrell et al, 1991;Marshall, Cooper, Rippon, & Patak, 1993;O'Donnell & Maddrell, 1995;Spring & Hazelton, 1987). Ca 2+ is moved from cell-to-lumen thermodynamically uphill by active Ca 2+ exporting pumps since both chemical (∼1000-fold) and electrical (V apical = +71 mV lumen-positive) gradients across apical membranes of A. domesticus tubules oppose Ca 2+ entry into the lumen (Coast, 2012). Plasma membrane Ca 2+ -ATPase (PMCA) pumps have been localized to the apical membranes in tubules of the gypsy moth, Lymantria dispar (Pannabecker, Smith, Beyenbach, & Wasserman, 1995).…”
Section: Secretion Of Ca 2+ and The Nature Of Apical Calcium Transportmentioning
confidence: 99%
“…Transporters include the Na + -K + -2Clcotransporter (NKCC, which imports Na + , K + , and Clacross the basolateral cell membrane), carbonic anhydrase (CA, which provides cytosolic protons), and V-ATPase (which pumps protons to the lumen for future exchange with intracellular cations; Chintapalli et al, 2013;Coast, 2012;Halberg et al, 2015). Highly convoluted, mitochondria-dense paracellular channels in the rectal pads form the scalariform complex, in which membrane-bound Na + -K + ATPase (NKA) establishes a high extracellular [Na + ].…”
Section: Introductionmentioning
confidence: 99%
“…In the meantime, these two drugs demonstrated similar preventative and therapeutic effects on various arrhythmias triggered by BaCl 2 or aconitine. It is well established that infusion of BaCl 2 leads to delayed afterdepolarization and triggered activity through increases in Na + and Ca 2+ inflow to the myocardium, promoting the genesis of arrhythmia (25,26). Most importantly, electrophysiological studies have found that Ba 2+ was the potential blocker of various K + channels and permeation of Ba 2+ through the K + channel may impede the presence of K + in the external solution, which may result in the increase of autorhythmicity of the myocardium to produce ventricular arrhythmia (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%